Metal allergy and the use of custom implants in primary total ankle replacement - Jay S. Badell, DPM, MS, AACFAS; James M. Cottom, DPM, FACFAS (Foot & Ankle Surgery: Techniques, Reports & Cases, 2023)
Purpose: Patients with metal allergy often go undiagnosed prior to surgery. This can lead to a high rate of complications, especially with orthopedic implants which can be highly variable in the composition of metals used in their production. The purpose of this technique guide is to highlight the use of pre-operative allergy testing in patients with known history of metal allergy, emphasize the proper steps in identifying a potential metal sensitivity reaction, and to report in literature the success of primary custom printed total ankle arthroplasty implants manufactured without the use of traditional metal compositions. Technique guide: Patients often have undergone treatment in the past, but nevertheless, discussion about all treatment options, both conservative and surgical should be addressed. The author's preference is to maintain motion in the ankle joint if safe and reasonable. Often times patients will be unaware of metal allergy unless they have had prior reaction, usually from a previous orthopedic surgery. In the cases where the patient does report previous hypersensitivity reaction to metals, referral should then be made to an Allergist for comprehensive metal patch testing or lymphocyte transformation testing. Once the metal limitations are identified, orthopedic industry partner with custom printing capabilities is then contacted. Working with engineers, ankle implants free of offending metals are able to be manufactured. Analysis & discussion: To the author's knowledge, very few cases of metal sensitivity to total ankle replacement exist in the literature. The author's experience to date has shown favorable results when metal allergy is identified, particularly in patients with known history of metal allergy. With proper pre-operative planning and industry partner, good outcomes can be achieved in patients with metal allergy undergoing primary total ankle arthroplasty.